Automated farming system using distributed controller: a feasibility study - Rashid, Muhammad Mahbubur; Sall, Alioune; Hasan, Tahsin F (AlamBiblio Publishers, 2021)
Agriculture is fundamental toa human being because it has itranted humanity's evolution. It is among the essential activities that ensure the development of the human being. So, it is capital to ensure good work and the efficiency of agricultural production. Thus, the research is focused on the domain of agriculture automation to increasethe agriculture production yield with less water consumption and less risk in Africa, particularly in Senegal,where agriculture delays reachingfood self-sufficiency because of rudimentary materials. The farmers are using a hilar, plough, and hoe for doing their daily tasks. The watering can still be used to water a large area of crops andis done randomly. The chemical pesticide is done manually using a manual sprayer, which causes enormous risks of diseases to the farmers anddestroys the field and even the crops. This thesis describes an approach toautomated farming by the use of a Sprayer Robot based on Arduino. Besides the Sprayer Robot, the paper also presents an automated irrigation system based on the Senegalese climatic parameters and soil textures throughCROPWAT and CLIMWAT. The automaticirrigation system is done with a programmable logic controller,the master controller of the overall design,including the Sprayer Robot. Moreover, a SCADA graphical interface is also implemented for the monitoring of the whole system. The project, tested in simulation with theCROPWAT and CLIMWAT data, could give no reduction yield if applied and also reduced risk of diseases due to chemicals